Accountability and the pressures to exclude: A cautionary tale from England. - Rustique-Forrester, E. (Education Policy Analysis Archives, 2005)
Recent studies have produced conflicting findings about whether test-based rewards and sanctions create incentives that improve student performance, or hurdles that increase dropout and pushout rates from schools. This article reports the findings from a study that examined the impact of England's accountability reforms and investigated whether the confluent pressures associated with increased testing, school ranking systems, and other sanctions contributed to higher levels of student exclusion (expulsion and suspension). The study found that England's high-stakes approach to accountability, combined with the dynamics of school choice and other curriculum and testing pressures led to a narrowing of the curriculum, the marginalization of low-performing students, and a climate perceived by teachers to be less tolerant of students with academic and behavioral difficulties. A comparison of higher- and lower-excluding schools, however, found that these effects were more pronounced in the higher-excluding schools, which lacked strong systems and internal structures for supporting staff communication, teacher collaboration, and students' individual needs. The study offers an international perspective on recent trends toward greater accountability in education, pointing to a complex inter-relationship between the pressures of national policies and the unintended consequences on schools' organizational and teachers' instructional capacities. The study's findings raise particular implications for the United States and show that in the design of accountability systems, attention must be paid to how the pressures from accountability will affect the capacity of schools and teachers to respond to students who are low-performing and struggling academically.